Comparative Evaluation of Ultrasonography and Cross-sectional Imaging in Determining Gall Bladder Perforation in Accordance to Niemeier’s Classification - Boruah, Deb K. (J Clin Diagn Res, 2016)
INTRODUCTION: Gall Bladder (GB) perforation, a rare but dreaded complication of acute cholecystitis and is associated with high mortality rate. Early detection of acute cases of GB perforation reduces the risk of biliary peritonitis and hence the associated mortality and morbidity. AIM: The purpose of the study was to make a comparative evaluation of the role of Cross-sectional imaging in GB perforation with base line investigation like sonography. Finally both modalities were compared in determining the type of perforation according to Niemeier’s classification. MATERIALS AND METHODS: We retrospectively evaluated the Ultrasonography (USG), Computed Tomography (CT) and Magnetic Resonance Imagings (MRI) findings in patients of GB perforation with surgical correlation. RESULTS: We evaluated 17 patients of GB perforations over a time period of one year. USG was done in all patients. As cross-sectional modality only CT scan was done in 14 patients and MRI scan was done in four patients. Both CT and MRI scans were done in one patient. CONCLUSION: Cross-sectional imaging must not be delayed in suspected cases of GB perforations because it helps in establishing a quicker diagnosis, detecting complications and also helps in decision making related to management thereby reducing the morbidity and mortality associated with this condition.